Safety evaluation of very high doses of intravitreal topotecan in rabbits - del Sole, Maria Jose (2024)
Introduction Intravitreal topotecan (TPT) at 90 μg has shown promise for treating intraocular retinoblastoma. However, the control of refractory or recurrent vitreous seeds and retinal tumors remains a challenge and these difficult-to-treat eyes may require higher doses than those currently used in the clinic. Objectives To evaluate systemic and ocular safety of monthly very high-doses intravitreal injections of TPT in rabbits. Methods Systemic and ocular toxicity was assessed in non-tumor-bearing New Zealand rabbits after three monthly intravitreal injections of sterile water, 50 μg, 100 μg or 200 μg of TPT into one eye and vehicle into the contralateral. Animals were evaluated monthly for general and ophthalmic clinical status including direct and indirect ophthalmoscopy, biomicroscopy, and scotopic electroretinography (ERG). One month after the last injection, the eyes were enucleated and subjected to histological assessment. Linear mixed effects models were used for the statistical analysis of the treatment effects. Results Weight, hair loss, or changes in hematologic values were absent during the study period across all animal groups. No evidence of retinal or optic nerve alterations were evidenced by fundus examination except in 2 eyes treated with 200 μg TPT that showed attenuation of retinal vasculature. Histological examination revealed no distinct abnormalities except for one eye treated with 200 μg TPT that showed a focus area of retinal distortion with loss of photoreceptors and gliosis. In line, a significant decrease in the a- and b-wave amplitudes of the ERG recording was registered for the group of eyes treated with 200 μg TPT despite ERG parameters remained within normal values for visual function. Conclusion Intravitreal TPT up to 100 μg per dose was safe in the rabbit’s eye. The results suggest a promising potential for clinical application of doses up to 200 μg TPT in relapse/refractory cases of retinoblastoma.